Strategies for Developing a School Work Climate to Enhance Teachers’ Achievement Motivation - M. Hanif Satria Budi; Khoirotul Izzah (International Journal of Technology and Education Research, 2026)
This study is motivated by the importance of a positive school work climate in enhancing teachers’ achievement motivation amid the demands of modern education. The problems addressed include the role of the principal, strategies for developing the school work climate, and their impact on teachers’ motivation at MTsN 2 Tulungagung. This research aims to analyze the strategies used to create a conducive work environment that supports teacher performance and achievement. This study employs a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation involving the principal, teachers, and educational staff. Data analysis was conducted using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings indicate that the development of the work climate is carried out through managerial strategies, professional development, provision of facilities, and strengthening of social relationships. Communicative leadership, appropriate task distribution, and reward systems are key factors in improving teachers’ work comfort. In addition, adequate facilities and professional development activities further enhance teachers’ achievement motivation. The impact of a conducive work climate is reflected in increased self-confidence, responsibility, achievement motivation, and professional performance of teachers. Therefore, effective management of the school work climate plays a crucial role in improving the quality of education in madrasahs.